ANALYSIS OF THE TOURISM SECTOR IN INDONESIA USING THE INPUT-OUTPUT AND ERROR-CORRECTION MODEL APPROACH - Hasudungan, Albert; Raeskyesa, Dewa Gede Sidan; Lukas, Erica Novianti; Ramadhanti, Fati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2021)
ABSTRACTThis research explores the role of the tourism sector in Indonesia, including its backward and forward linkages with other economic sectors. The tourism sector is represented by the hotel and restaurant (hospitality) industry. The study uses the input-output method and traces the econometric backward and forward shocks of the tourism sector with the Error Correction Model (ECM), using database from Statistics Indonesia from 2010 to 2019. The paper contributes to the existing literature by using multi-stage quantitative processes to observe backward and forward economic linkages. The result shows that manufacturing output contributes a significant and positive effect to the hotel and restaurant industry. At the same time, the tourism sector provides a significant and positive contribution to government retribution. Nonetheless, there is a negative relationship between the growth of the agriculture and tourism sector, which is assumed due to the tradeoff in the factor of production between the agricultural and tourism sector development. Consequently, backward and forward relationships suggest more holistic and prudent economic policies for observing interdependent tourism development in Indonesia's other economic sectors.  ABSTRAKTujuan penelitian ini adalah menginvestigasi keterkaitan ke belakang dan ke depan antara sektor pariwisata dan sektor ekonomi lain di Indonesia. Pariwisata di sini di wakili sektor perhotelan dan restoran. Studi ini menggunakan metode input-output dengan data berasal dari database input output Bank Pembangunan Asia (ADB). Kedua, studi menelusuri  keterkaitan ekonometrik ke depan dan ke belakang pariwisata dengan model koreksi kesalahan (ECM), menggunakan data triwulan dari PDB riil di database BPS dari tahun 2010 hingga 2019. Kontribusi makalah ini adalah proses multi-asesment untuk mengamati keterkaitan ekonomi ke belakang dan ke depan antara pariwisata dengan sektor ekonomi lainnya. Dari ekonometri tersebut, diketahui bahwa kontribusi output industry manufaktur berpengaruh signifikan dan positif terhadap industri hotel dan restoran. Selain itu, pariwisata memberikan kontribusi yang signifikan dan positif untuk retribusi pemerintah. Meskipun demikian, peningkatan output pariwisata datang dengan pengorbanan pengurangan output sektor pertanian. Hal ini dipengaruhi oleh kompetisi akses faktor produksi di antara kedua sektor tersebut. Hasil ini  menekankan perlunya kebijakan ekonomi yang lebih holistik dan hati-hati terhadap saling ketergantungan antara pembangunan pariwisata dengan sektor ekonomi lain di Indonesia.